2018
DOI: 10.1038/sdata.2018.213
|View full text |Cite
|
Sign up to set email alerts
|

Methylome of human skeletal muscle after acute & chronic resistance exercise training, detraining & retraining

Abstract: DNA methylation is an important epigenetic modification that can regulate gene expression following environmental encounters without changes to the genetic code. Using Infinium MethylationEPIC BeadChip Arrays (850,000 CpG sites) we analysed for the first time, DNA isolated from untrained human skeletal muscle biopsies (vastus lateralis) at baseline (rest) and immediately following an acute (single) bout of resistance exercise. In the same participants, we also analysed the methylome following a period of muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
114
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(134 citation statements)
references
References 19 publications
20
114
0
Order By: Relevance
“…Importantly, the largest increases in hypomethylation, gene expression and muscle mass were observed after later reloading/retraining. Therefore, the level of UBR5 gene expression was positively and strongly correlated with the increases in lean leg mass during periods of training and retraining (Seaborne et al 2018b). These data indicated that UBR5 was an E3 ligase associated with muscle hypertrophy rather than muscle atrophy.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Importantly, the largest increases in hypomethylation, gene expression and muscle mass were observed after later reloading/retraining. Therefore, the level of UBR5 gene expression was positively and strongly correlated with the increases in lean leg mass during periods of training and retraining (Seaborne et al 2018b). These data indicated that UBR5 was an E3 ligase associated with muscle hypertrophy rather than muscle atrophy.…”
Section: Introductionmentioning
confidence: 79%
“…The full biopsy procedure and the primary cell isolation procedures have been described previously (Seaborne et al . ; Seaborne et al . ; Turner et al .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a previously uncharacterized HECT domain E3 ligase called UBR5 (or EDD1) was found to be hypomethylated after resistance exercise‐induced hypertrophy in humans (Seaborne et al . , b ). In this study, the methylation profile of UBR5 appeared to be inversely correlated with changes in UBR5 gene expression, and the expression of UBR5 was positively correlated with the gains in lean leg mass during training and retraining.…”
mentioning
confidence: 99%